Pragmatic resistance as counter-conduct : civil society advocacy in Singapore - Neo, Isaac Yi Chong (Nanyang Technological University, 2020)
Discussions about civil society in Singapore often highlight how the state limits and controls civil society space. Consequently, the literature on civil society in Singapore is highly state-centric, focusing on the ways that civil society is constrained or co-opted by the state. As a result, the strategies that civil society actors use to negotiate and expand the space they can operate within are under-theorised. This dissertation analyses the methods that civil society actors use to engage the state and posits that civil society actors engage in pragmatic resistance against the state using largely non-confrontational and technocratic methods while strategically shifting between cooperating with and contesting the state. These less overt forms of resistance are acts of counter-conduct that simultaneously reproduce and contest the pragmatic governmentality of the state, expanding the spaces available for civil society to engage the state. This dissertation examines how civil society actors in the environmental and migrant worker sectors engage the state and how their methods of pragmatic resistance embody a pragmatic rationality while resisting it at the same time. This study hence offers a conceptual framework of pragmatic resistance as counter-conduct that can be used to analyse the activities of other civil society groups in Singapore as well as other countries where civil society actors are constrained politically.